Dual-spectra encoded suspension array using reversed-phase microemulsion UV curing and electrostatic self-assembling. Issue 38 (11th June 2018) - Feng, Guangxia; He, Qinghua; Xie, WenYue; He, Yonghong; Chen, Xuejing; Wang, Bei; Lu, Bangrong; Guan, Tian
Abstract : The rapid growth of demand for high-throughput multiplexed biochips from modern biotechnology has led to growing interest in suspension array based on multi-channel encoded microbeads. Abstract : The rapid growth of demand for high-throughput multiplexed biochips from modern biotechnology has led to growing interest in suspension array based on multi-channel encoded microbeads. We prepare dual-spectra encoded PEGDA microbeads (DSEPM) by reversed-phase microemulsion UV curing method and layer-by-layer electrostatic self-assembly method. Excitation of the synthesized DSEPM results in two spectra, including fluorescence spectra from quantum dots and laser induced breakdown spectra from nanoparticles with specific elements. With further surface modification and bio-probes grafting, we use DSEPM to carry a series of detection experiments of biomolecules. The adsorption experiment to two types of anti-IgG in mixture sample has demonstrated the availability of DSEPM in multiplexing. Then, the contrast experiment has verified the specificity of DSEPM in detection. Finally, we carry out the concentration gradient experiment and obtain the response curve to show the performance of DSEPM in quantitative analysis. The results indicate our method provide an effective way to improve multiplexed biochips with more coding capacity, accuracy and stability.